Untamed Urbanisms - Allen, Adriana; Lampis, Andrea; Swilling, Mark (Routledge Advances in Regional Economics, Science and Policy, 2016)
An electronic version of this book is available Open Access at www.tandfebooks.com. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. One of the major challenges of urban development has been reconciling the way cities develop with the mounting evidence of resource depletion and the negative environmental impacts of predominantly urban-based modes of production and consumption. This book aims to re-politicise the relationship between urban development, sustainability and justice, and to explore the tensions emerging under real circumstances, as well as their potential for transformative change. For some, cities are the root of all that is unsustainable, while for others cities provide unique opportunities for sustainability-oriented innovations that address equity and ecological challenges. This book is rooted in the latter category, but recognises that if cities continue to evolve along current trajectories they will be where the large bulk of the most unsustainable and inequitable human activities are concentrated. By drawing on a range of case studies from both the global South and global North, this book is unique in its aim to develop an integrated social-ecological perspective on the challenge of sustainable urban development. Through the interdisciplinary and original research of a new generation of urban researchers across the global South and North, this book addresses old debates in new ways and raises new questions about sustainable urban development. .